Poética da ausência materna - Agostini, Stéfani Trindade (2021)
This dissertation addresses the theme of maternal absence in a visual poetics developed based on the researcher's personal history. The research aimed to investigate poetic possibilities related to the figuration of maternal absence. It used, as a methodological foundation, an approach derived from autoethnography adapted to research in visual arts. As a result, fourteen works were developed that are part of two series: the first series addresses the poetics of maternal absence, through subtractive acts performed in digital media and proposes a visuality mediated by inkjet transfers on rag paper; the second works this absence through substitutive forms in the midst of installations composed with materials that suggest a synesthetic approach. It concludes that the use of the autoethnographic approach, during the poetic research, makes it possible to deepen the understanding of some aesthetic and cultural aspects of the works through reflection on the relationships established between the researcher's personal contexts and the contemporary social context. And that the works presented materialize visual possibilities with the potential to provoke the experience of presence from figurative absences.